THE PRENATAL NURSING CONSULTATION FROM THE PERSPECTIVE OF KRISTEN SWANSON'S THEORY OF CARE - Renata Lafaiete Cardoso Paes; Diego Pereira Rodrigues; Valdecyr Herdy Alves; Sílvio Éder Dias da Silva; Carlos Leonardo Figueiredo Cunha; Márcia Simão Carneiro; Tatiana do Socorro dos Santos Calandrini (Universidade Federal do Paraná, 2022)
Objective: to understand the meanings attributed by Amazonian women regarding the prenatal nursing consultation. Method: descriptive, exploratory, and qualitative study, conducted through semi-structured interviews with the participation of 14 pregnant women in a basic health unit in the State of Pará, Brazil, between the months of August and November 2020. Data were transcribed and submitted to content analysis and supported based on the optics of Kristen Swanson's Theory of Care. Results: prenatal care must be focused on creating a bond and the Amazonian woman's singularity, allowing for her understanding to meet the women's specificities, articulating integral health care, a relationship of knowing and being with the woman and her family, for relationships of exchange and involvement, providing a link to maternal health. Conclusion: concepts from the theory of care allow the nurse to be with the woman and provide individualized, singular, particularized care within the context of prenatal care.